2019
DOI: 10.1002/ejic.201801451
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Balance of Cu+ and Oxygen Vacancies of CuOx‐CeO2 Composites for CO Oxidation Based on Thermal Treatment

Abstract: It is important to exploit non‐noble metal catalysts with excellent performance toward CO oxidation. Here, CuOx‐CeO2 composites with a size of about 4 nm have been fabricated by a facile and mild in situ route without solvent or liquid reactant involved. The balance between Cu+ concentration and oxygen vacancy on the CeO2 surface, which are beneficial for catalytic activity, can be tailored by the amount of Cu loading and the thermal treatment parameters of composites. The as‐obtained CuOx‐CeO2 (C‐9‐6‐C) compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The difference in catalytic performance between SACs and AuAu/SiO 2 may derive from the strong synergistic effect from the CeO 2 shell. As a typical reducible support with oxygen storage capability, CeO 2 with abundant oxygen vacancy defects can adjust the Ce 3+ /Ce 4+ ratio depending on the redox conditions . And the CeO 2 shell with excellent redox and oxygen storage capability facilitates the CO oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in catalytic performance between SACs and AuAu/SiO 2 may derive from the strong synergistic effect from the CeO 2 shell. As a typical reducible support with oxygen storage capability, CeO 2 with abundant oxygen vacancy defects can adjust the Ce 3+ /Ce 4+ ratio depending on the redox conditions . And the CeO 2 shell with excellent redox and oxygen storage capability facilitates the CO oxidation process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Liu et al [52] observed the maximum CO oxidation activity of Cu x -CeO 2 catalyst due to strong interaction between CuOx and CeO 2 . The optimum amount of Cu doping on CeO 2 and its calcination temperature showed significant effect on catalytic performance than pure CeO 2 .…”
Section: Co Oxidation Using Modified Ceomentioning
confidence: 99%
“…In the past few decades, many transition metal oxide catalysts have been developed, mainly including CeO 2 [ 13 , 21 , 22 ], MnO 2 [ 23 , 24 , 25 ], Co 3 O 4 [ 26 , 27 , 28 ], CuO [ 29 , 30 , 31 ], Fe 2 O 3 [ 32 , 33 , 34 ] et al, Co 3 O 4 -CeO 2−x [ 16 , 35 ], Cu-Mn [ 36 ], Ce-Cu [ 37 , 38 ], and Ce-Mn [ 39 , 40 ] composite oxides. Different active metals and carriers will result in different interactions between metals and carriers and different exposed active sites, thus making them have different reactivity for CO catalytic oxidation.…”
Section: Introductionmentioning
confidence: 99%